Microscopic observation on the effect of chlorhexidine and hydrogen peroxide on human corneal epithelial cell line - Abd Manaf, Ali; Fatimah, Hashim; Nakisah, Mat Amin (2013)
Chlorhexidine (CHX) and hydrogen peroxide (H2O2) are among ingredients used in contact lens disinfecting solution, and had been used for eye treatment due to microbial infection. However, both chemicals have been reported to cause inflammation to the cornea and the symptoms that are related such as eye irritation and ulcers of the cornea. In this study, the cytotoxic potential of CHX and H2O2 were evaluated through the establishment of dose response and 50 % inhibition concentration (IC50) values on human corneal epithelial cell (HCEC) line by MTT colorimetric assays, while cytotoxicity and genotoxicity approach were investigated by light and fluorescence microscopy.The effects of CHX and H2O2 at the genomic level on the HCEC were observed and quantified by using alkaline comet assay. An observation under light microscopy showed the untreated HCE cells with intact and prominent nucleus while CHX- treated HCEC showed dark precipitates accumulated in the cell’s cytoplasms. The HCEC treated with H2O2 however, were seen with swelling of cells and their cytoplasmic content. Under fluorescence microscopy, untreated HCEC when stained with acridine orange and propidium iodide fluoresced green with a green intact nucleus indicating the cells were viable and healthy. CHX-treated HCE cells however, were observed with orange-red nuclei indicating necrotic type of cells. HCE cells treated with H2O2 showed typical criteria of apoptotic cells when blebbing of cytoplasm and yellow nucleus were observed. Interestingly, genotoxicity testing by alkaline comet assay conducted in the present study indicated that only H2O2 showed genotoxicity effects on the HCEC after two hour treatment. Therefore, observation in this study has proved that the cytotoxic and genotoxic effects of CHX and H2O2 on HCEC could be analyzed and confirmed by using both light and fluorescence microscopy